2017
DOI: 10.1186/s12862-017-0989-9
|View full text |Cite
|
Sign up to set email alerts
|

Dated tribe-wide whole chloroplast genome phylogeny indicates recurrent hybridizations within Triticeae

Abstract: BackgroundTriticeae, the tribe of wheat grasses, harbours the cereals barley, rye and wheat and their wild relatives. Although economically important, relationships within the tribe are still not understood. We analysed the phylogeny of chloroplast lineages among nearly all monogenomic Triticeae taxa and polyploid wheat species aiming at a deeper understanding of the tribe’s evolution. We used on- and off-target reads of a target-enrichment experiment followed by Illumina sequencing.ResultsThe read data was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
112
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(140 citation statements)
references
References 105 publications
20
112
0
Order By: Relevance
“…tauschii branch, 20.3 major rearrangements per MY, were applicable to the entire tribe, the Ae. tauschii lineage would be expected to accumulate 203 major rearrangements over the 10-MY period, the estimated divergence time of the wheat and barley lineages and the age of Triticeae (Dvorak and Akhunov, 2005;Bernhardt et al, 2017). This number exceeds the total number of 175 major rearrangements that the Ae.…”
Section: Rates Of Genome Evolutionmentioning
confidence: 98%
See 2 more Smart Citations
“…tauschii branch, 20.3 major rearrangements per MY, were applicable to the entire tribe, the Ae. tauschii lineage would be expected to accumulate 203 major rearrangements over the 10-MY period, the estimated divergence time of the wheat and barley lineages and the age of Triticeae (Dvorak and Akhunov, 2005;Bernhardt et al, 2017). This number exceeds the total number of 175 major rearrangements that the Ae.…”
Section: Rates Of Genome Evolutionmentioning
confidence: 98%
“…The hexaploid genome of bread wheat is thus a product of convergence of three diploid Triticeae lineages, those of the A, B and D genomes. Their divergence was estimated to have occurred between 1.4 and 4.5 million years ago (MYA) (Huang et al, 2002;Dvorak and Akhunov, 2005;Gornicki et al, 2014;Middleton et al, 2014;Bernhardt et al, 2017), although a time as ancient as 7 MYA has also been suggested (Marcussen et al, 2014). An average divergence time of 3 MY will be used throughout this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite prior cytogenetic and phylogenetic studies (e.g. Meimberg et al 2009;Bernhardt et al 2017), diploid progenitors and the recurrent origins of allopolyploid wild wheats were not precisely identified. Accordingly, we first infer the reticulate phylogeny of allopolyploids using plastid and nuclear loci to provide a robust comparative framework.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations have sequenced and compared complete plastid genome sequences over the past decade (Gao et al, 2010;Gitzendanner et al, 2018b), and the number of publicly available plastid genomes continues to increase dramatically (Tonti-Filippini et al, 2017). Recent studies on plastid genome structure and evolution now evaluate polymorphisms across hundreds of genome sequences (Bernhardt et al, 2017;Teisher et al, 2017;Saarela et al, 2018;Gitzendanner et al, 2018a), rendering the precise assembly process of plastid genomes and its quality assessment ever more important.…”
mentioning
confidence: 99%